2000
DOI: 10.1054/bjoc.2000.1490
|View full text |Cite
|
Sign up to set email alerts
|

Timing within the menstrual cycle, sex, and the use of oral contraceptives determine adrenergic suppression of NK cell activity

Abstract: Physiological responses that involve adrenergic mechanisms, such as stress-induced changes in cardiovascular indices, were reported to fluctuate along the menstrual cycle. Metastatic development following surgery was also reported to vary according to the menstrual phase during which a primary breast tumour was removed. Natural killer (NK) cells are believed to play an important role in controlling metastases. Our recent studies in rats demonstrated that adrenergic suppression of NK activity and of resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Our analysis showed that experimental stress applied during the luteal phase deteriorated the immune system more since the CD4+/CD8+ cell ratio and NK cell number were lower in this group compared to the follicular phase. This finding points out that women behave differently during the different phases of the menstrual cycle and they may be more vulnerable to immune system-related diseases during the luteal phase, as was also suggested by Shakhar et al [46] and Mo et al [47] . The lowest CD4+/ CD8+ T lymphocyte ratio was found in posttest samples obtained from men; together with the decrease in NK cell number this finding suggests a shift of the immune response to probably humoral immunity as we have shown previously [2] , but the change in NK cells was not due to increased apoptosis in the present study but most likely due to recompartmentalization as suggested by Dhabhar [29] .…”
Section: Discussionsupporting
confidence: 77%
“…Our analysis showed that experimental stress applied during the luteal phase deteriorated the immune system more since the CD4+/CD8+ cell ratio and NK cell number were lower in this group compared to the follicular phase. This finding points out that women behave differently during the different phases of the menstrual cycle and they may be more vulnerable to immune system-related diseases during the luteal phase, as was also suggested by Shakhar et al [46] and Mo et al [47] . The lowest CD4+/ CD8+ T lymphocyte ratio was found in posttest samples obtained from men; together with the decrease in NK cell number this finding suggests a shift of the immune response to probably humoral immunity as we have shown previously [2] , but the change in NK cells was not due to increased apoptosis in the present study but most likely due to recompartmentalization as suggested by Dhabhar [29] .…”
Section: Discussionsupporting
confidence: 77%
“…These effects are mediated through activation of leukocyte membrane receptors for these ligands, and intracellular initiation of the cAMP-PKA cascade common to both receptor systems [59, 60]. Potentially underlying the aforementioned sex differences in the impact of catecholamines on NKCC are the (i) menstrual cycle and female gonadal hormones that were shown to affect human and rat NK cell susceptibility to adrenergic stimulation [24, 61], presumably through modulating expression levels of adrenergic receptors on leukocytes [62], and (ii) testosterone that was shown to increase rat susceptibility to adrenergic suppression of in vivo levels of NKCC [55]. …”
Section: Discussionmentioning
confidence: 99%
“…This assertion is supported by several characteristics of the RCT and other studies indicating the perioperative effects of sex hormones on cancer outcomes, specifically, that they were observed in women with positive but not negative lymph nodes, were due to distal malignant recurrence, were not evident before 3 years post-surgery, and were independent of tumour hormone receptor status. 11,128 These observations suggest that surgery potentiated an ongoing metastatic process, not through direct effects of sex hormones on the malignant tissue (as it was independent of receptor status), but through an indirect mechanism, such as immunosuppression 131,132 or other processes that facilitate progression of an early stage of a metastatic process. 11,127 …”
Section: Surgical Aspects Affecting Recurrencementioning
confidence: 99%